IMPLEMENTASI LAYANAN BIMBINGAN KLASIKAL SEBAGAI UPAYA PENGUATAN KESEHATAN MENTAL WARGA BINAAN DI LAPAS KELAS III RANGKASBITUNG - Irfan, Muhammad Dwi; Prabowo, Arga Satrio; Wahyuningsih, Lenny; Angga Sugara Febriantiko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Due to limited space, social pressure, and inadequate psychological services,Rangkasbitung Class III Correctional Facility experiences approximately 200%overcrowding (321 inmates compared to a capacity of 100), highlighting the urgentneed for a mental health strengthening program. This community service initiativeaimed to implement classical guidance services to reduce inmates’ stress, anxiety,and depression. The program was conducted from September to December usinga Community-Based Participatory Research (CBPR) approach through needsassessment, collaborative planning, service implementation, and evaluation. ADASS-21 assessment was administered to 70 early-adult inmates; 32 inmates wereselected as the sample, and pretest–posttest evaluation was analyzed for 26inmates who completed the entire program. The results showed a significant changein categories, where in the posttest all participants were in the normal-moderatecategory (100%) for depression, anxiety, and stress, and no longer found the severeor very severe categories. These findings indicate that classical guidance services,supported by group activities and counseling, effectively strengthen inmates’emotional regulation and coping strategies and are relevant to be developed as asustainable mental health development program in correctional settings.